Red meat and processed meat intake and risk of cutaneous melanoma in white women and men: Two prospective cohort studies - Yen, Hsi (J Am Acad Dermatol, 2018)
BACKGROUND: Red and processed meat consumption has been associated with increased risk of several cancers, but association with cutaneous melanoma risk has been inconclusive. OBJECTIVE: To investigate the association between red and processed meat intake and melanoma risk. METHODS: Dietary information was assessed using food frequency questionnaires in two prospective cohorts - 75,263 women from the Nurses’ Health Study (1984 – 2010) and 48,523 men from the Health Professionals Follow-up Study (1986 – 2010). Melanoma cases were confirmed by review of pathological records. Pooled multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazards models. RESULTS: A total of 679 female and 639 male melanoma cases were documented during follow-up. Red and processed meat intake was inversely associated with melanoma risk (P for trend = 0.002); the pooled HRs (95% CIs) of the two cohorts were 1.00 (reference), 1.00 (0.87 – 1.14), 0.98 (0.86 – 1.13), 0.89 (0.77 – 1.02), and 0.81 (0.70 – 0.95) for increasing quintiles of intake. LIMITATIONS: Findings may have limited generalizability, as the cohorts were limited to white health professionals. CONCLUSION: Red and processed meat intake was inversely associated with melanoma risk in these two cohorts.